A 5-Year Update on the Clinical Development of Cancer Cell-Based Vaccines for Glioblastoma Multiforme - Almohanad A. Alkayyal; Ahmad Bakur Mahmoud (Pharmaceuticals)
Glioblastoma multiforme (GBM) is considered one of the most aggressive forms of brain cancer with a 15-month median survival, despite advancements in surgery, radiotherapy, and chemotherapy. The immune-suppressed tumor microenvironment and the blood–brain barrier are major contributors to its poor prognosis and treatment resistance. In the last decade, significant progress has been made in developing cell-based vaccines to boost immune responses against GBM. This review provides an extensive update on recent clinical trials involving various cancer cell vaccines, including ICT-107, the α-type-1 DC vaccine, and others. Although these trials have demonstrated potential improvements in progression-free survival (PFS) and overall survival (OS), the diverse and immune-suppressed nature of GBM poses challenges for consistent therapeutic success. We discuss the details of these trials along with the potential mechanism of vaccine efficacy and immune activations. The findings of these trials highlight the significance of a personalized immunotherapy approach and suggest that patient stratification could significantly advance the clinical management of GBM.